Count! - Fleming, Denise, 1950- (New York : H. Holt, 1992)
The antics of lively and colorful animals present the numbers one to ten, twenty, thirty, forty, and fifty.
Publishers Weekly Editors' Choice
*SLJ*
Booklist
1.6
K-3
Keywords: Counting -- Juvenile literature; Animals -- Juvenile literature; Counting; Animals; Counting; Animals